Present status of laboratory teaching in the department of Pathology of undergraduate medical education in Bangladesh (Bangladesh Journal of Medical Education, 2017)
Introduction: Effective laboratory teaching and practical work has an important and time-honored place in the education of students and researchers. The main principle underlying laboratory work is that students learn effectively through doing practical tasks (learning by doing). The laboratory courses offer students the opportunity to gain manipulative skills, observational skills, and the ability to plan experiments and to interpret experimental data.Justification: There is less involvement and less active participation in the pathology practical classes by the students. Little has been published about the actual problem. Therefore this study was designed to investigate the ways of conduction of laboratory teaching in different medical colleges of Bangladesh.Objectives: The aim of this study was to explore the present status of laboratory teaching in the department of Pathology of undergraduate medical education in Bangladesh.Materials and methods: This descriptive cross sectional study was carried out to determine the ways of conduction of laboratory teaching in Pathology department of undergraduate medical education in Bangladesh. The study was carried out in Eleven (Five Government and Six Non- Government) medical colleges in Bangladesh over a period from July 2014 to June 2015 by adopting convenience sampling. Triangulation technique was used in this study to ensure the validity and reliability of research findings. For each variable of structured observation and structured questionnaires, the mean score was calculated.Results: From observation of the study, it was found that among physical environment factors, the mean score of seating arrangement, space available for practical work in the class and teacher student ratio were >3 but 2 but 2 but 4but